2016
DOI: 10.1002/jcsm.12146
|View full text |Cite
|
Sign up to set email alerts
|

Exercise rehabilitation following intensive care unit discharge for recovery from critical illness: executive summary of a Cochrane Collaboration systematic review

Abstract: Skeletal muscle wasting and weakness are major complications of critical illness and underlie the profound physical and functional impairments experienced by survivors after discharge from the intensive care unit (ICU). Exercise‐based rehabilitation has been shown to be beneficial when delivered during ICU admission. This review aimed to determine the effectiveness of exercise rehabilitation initiated after ICU discharge on primary outcomes of functional exercise capacity and health‐related quality of life. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
4

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 46 publications
0
58
0
4
Order By: Relevance
“…The beneficial effect of resistance exercise training was also observed on sarcopenia and dynapenia in breast cancer patients receiving adjuvant chemotherapy . However, in a meta‐analysis review on the effectiveness of exercise rehabilitation after intensive care unit discharge on functional exercise capacity and health‐related quality of life was unable to find an overall effect on these parameters . A novel interesting therapy option is the use of neuromuscular electrical stimulation in HF patients.…”
Section: Sarcopenia In Heart Failurementioning
confidence: 99%
“…The beneficial effect of resistance exercise training was also observed on sarcopenia and dynapenia in breast cancer patients receiving adjuvant chemotherapy . However, in a meta‐analysis review on the effectiveness of exercise rehabilitation after intensive care unit discharge on functional exercise capacity and health‐related quality of life was unable to find an overall effect on these parameters . A novel interesting therapy option is the use of neuromuscular electrical stimulation in HF patients.…”
Section: Sarcopenia In Heart Failurementioning
confidence: 99%
“…87 An accelerometer-determined physical activity showed an independent, dose-response relationship with lean mass percentage and lower limb strength. 94 A novel treatment option in CHF patients is neuromuscular electrical stimulation, which has been deemed safe to use. 89 Interestingly, a significant plasticity of ageing skeletal muscle to adapt to resistancetype exercise training has been shown by transcriptomics after a 6 month training period including partial reversal of age-related changes in skeletal muscle gene expression.…”
Section: Chronic Heart Failure and Muscle Maintenancementioning
confidence: 99%
“…Foong et al studied 636 community-dwelling older adults with a mean age of 66 ± 7 years. 61 An interesting approach was presented by Chan et al who performed a randomized controlled trial of integrated care for patients with frailty and sarcopenia: 289 patients were randomized to one of two groups. Using accelerometer measurement, the authors found that physical activity intensity was positively associated with both lean mass percentage and lower limp strength in dose-response fashion.…”
Section: Physical Exercise and Rehabilitationmentioning
confidence: 99%